Leapfrogging: Time of Entry and Firm Productivity - Georg Götz; Josh Ederington (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We develop a model in which ex ante identical firms make endogenous entry and technology adoption decisions. We show that this model is capable of matching the stylized facts in which entry is dispersed over time and that, in many industries, it is the newest firms which are the most likely to exhibit high productivity growth and adopt new innovations (i.e., leapfrogging). We then derive the characteristics of those industries where such leapfrogging is likely to occur.
Keywords: L11; 330